The Influence of Big Data Implementation of Audit in Government Institutions (Study in Inspectorate Office Majalengka District) - Budi Karyanto (Syntax Corporation Indonesia, 2020)
The purpose of this study was to determine how much influence Big Data has on the audit process in government institutions. The research method used is to read and study manuscripts, reports and some other literature relating to the problem to be examined. So the results obtained by Big Data affect audit in government institutions.